Stimulus Fractionation by Interocular Suppression - Zadbood, Asieh; Lee, Sang-Hun; Blake, Randolph (Frontiers in Human Neuroscience, 2011)
Can human observers distinguish physical removal of a visible stimulus from phenomenal suppression of that stimulus during binocular rivalry? As so often happens, simple questions produce complex answers, and that is the case in the study reported here. Using continuous flash suppression to produce binocular rivalry, we were able to identify stimulus conditions where most – but not all -- people utterly fail to distinguish physical from phenomenal stimulus removal, although we can be certain that those two equivalent perceptual states are accompanied by distinct neural events. More interestingly, we find subtle variants of the task where distinguishing the two states is trivially easy, even for people who utterly fail under the original conditions. We found that stimulus features are differentially vulnerable to suppression. Observers are able to be aware of existence/removal of some stimulus attributes (flicker) but not others (orientation), implying that interocular suppression breaks down the unitary awareness of integrated features belonging to a visual object. These findings raise questions about the unitary nature of awareness and, also, place qualifications on the utility of binocular rivalry as a tool for studying the neural concomitants of conscious visual awareness.